1979
DOI: 10.1111/j.1752-1688.1979.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

PETROLEUM HYDROCARBONS IN URBAN RUNOFF1

Abstract: Estimates were made of petroleum hydrocarbon pollution loadings reaching the Delaware Estuary by determining storm event loadings of hydrocarbons from four storm sewers, draining areas of different land uses. Although refinery effluents constituted the largest source of petroleum pollution in 1975, it appears that after completion of currently required treatment processes urban runoff will be the largest remaining source of petroleum pollution. The petroleum in urban runoff resembles used crankcase oil in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Similarly, Heit (1985) determined that atmospheric deposition is the prime source of PAH's for Cayuga Lake, N.Y. Runoff into the Delaware River estuary between Trenton and Philadelphia has been found to contain both particulate and dissolved quantities of petroleum hydrocarbons, many of which were identified as PAH's (Whipple and Hunter, 1979). Naphthalene concentrations ranging from 1 to 4 mg!L have been reported by Jungclaus and others (1978) in the wastewater of a specialty chemicals manufacturing plant.…”
Section: Environmental Distributionmentioning
confidence: 97%
“…Similarly, Heit (1985) determined that atmospheric deposition is the prime source of PAH's for Cayuga Lake, N.Y. Runoff into the Delaware River estuary between Trenton and Philadelphia has been found to contain both particulate and dissolved quantities of petroleum hydrocarbons, many of which were identified as PAH's (Whipple and Hunter, 1979). Naphthalene concentrations ranging from 1 to 4 mg!L have been reported by Jungclaus and others (1978) in the wastewater of a specialty chemicals manufacturing plant.…”
Section: Environmental Distributionmentioning
confidence: 97%
“…Once deposited, PAHs accumulate in soils of the Seine Basin (Motelay-Massei et al, 2004) and can be subsequently removed from soil by runoff. Several studies showed that runoff is a major source of hydrocarbons for the coastal environment Whipple & Hunter, 1979;Hoffman et al, 1983Hoffman et al, , 1984Hoffman et al, , 1985Barrick & Prahl, 1987;Latimer, 1990;Fulton et al, 1993;Ashley & Baker, 1999). PAHs contained in runoff waters to the lower Seine join fluvial inputs coming from upper reaches of the Seine (e.g., Paris), at the dam of Poses.…”
Section: Introductionmentioning
confidence: 99%
“…An this led to the observation that the level of watershed development had the single, greatest anthropogenic influence on the temperature regime of urban, headwater streams. Whipple and Hunter (1979) determined that urban runoff is the largest remaining source of petroleum pollution. The petroleum in urban runoff resembles used crankcase oil in composition, and contains toxic chemicals such as polynuclear hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%